2005
DOI: 10.1002/uog.1799
|View full text |Cite
|
Sign up to set email alerts
|

Fetal lung volumetry using two‐ and three‐dimensional ultrasound

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
4
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 43 publications
4
114
4
8
Order By: Relevance
“…RaineFenning et al 8 demonstrated that this rotational technique is better than the conventional measuring method. After several in vitro 8 and in vivo [9][10][11] experiments, the VOCAL imaging application is now considered to be the 'gold standard' for volume measurements in ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%
“…RaineFenning et al 8 demonstrated that this rotational technique is better than the conventional measuring method. After several in vitro 8 and in vivo [9][10][11] experiments, the VOCAL imaging application is now considered to be the 'gold standard' for volume measurements in ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Desde então, pesquisas científicas comparam a tecnologia 3D com a 2D nas diversas áreas da medicina, testando a sensibilidade de ambos os métodos [15][16][17] .…”
Section: Discussionunclassified
“…The pathology from the fetal pneumonectomy demonstrated pulmonary hyperplasia consistent with bronchial atresia without evidence of CCAM-like changes. Serial ultrasound examinations demonstrated slow growth of the hypoplastic right lung to a maximum calculated volume of 17 ml 1 month postoperatively (mean normal right lung volume at 31 weeks' gestation is 27.7-28.53 ml) [8,9,10]. The fetal liver showed multiple areas of increased sonolucency concerning for areas of liver infarction believed to be a sequelae of the intraoperative fetal cardiac arrest (fig.…”
Section: Case Reportsmentioning
confidence: 99%